Practices of promoting cultural institutions on social networks: Trends and recommendations for children’s art schools - Elizaveta K. Plekhanova (Управление культурой)
Taking into account the increased interest in social networks, confirmed by VTsIOM data for 2023 (86% of surveyed Russians who use social networks spend time on them almost every day), the article examines the communities of music and art educational institutions in Yekaterinburg, Smolensk and Nizhny Novgorod in social network "VKontakte". They structurally and meaningfully study the features that unite them: visual design, the presence of basic data about the institution, the presence of information blocks for target audiences. The purpose of the study is to analyze the communities of institutions of additional art education for children in order to develop recommendations for improving the sites of these institutions on the social network VKontakte. Methods and results were used: 1. a comparison was made of these resources with the pages of commercial institutions on VKontakte offering music, drawing, and singing training services; based on the comparison, differences in design and content were shown; 2. communities of art and music educational institutions are also analyzed in the field of regularity of content publication, its main topics and social network tools; 3. techniques have been identified that are used to draw attention to the activities of institutions (graphic design of communities, the presence of basic information about the place, opening hours, ways to leave feedback), 4. the specifics of maintaining pages have been determined (unified information on important public topics, for example, prevention of HIV infection, reports on past events in Children's Art School, lack of useful content in comparison with informational ones) and areas for improving the quality of promotion on social networks were discovered. Recommendations for maintaining pages on social networks are formulated based on existing typical practices for promoting such institutions, as well as formats for promoting commercial institutions developing similar areas of education: focus on an “external” audience not only in publications, but also in the design of pages; establish channels of operational communication on pressing issues within the community; approve a single corporate style or colors when designing a page, as well as a clear publication schedule. It is also recommended to introduce entertaining and useful content, use different content formats offered by the social network, and use hashtags. Photo albums should be used not only for reporting, but also for business cards of teachers, posting reviews of the Children's School of Art and basic visual information about the institution.